Polyphosphate Kinase Mediates Antibiotic Tolerance in Extraintestinal Pathogenic Escherichia coli PCN033 - Chen, Jing; Su, Lijie; Wang, Xiangru; Zhang, Tao; Liu, Feng; Chen, Huanchun; Tan, Chen (Frontiers in Microbiology, 2016)
Extraintestinal pathogenic Escherichia coli (ExPEC) causes a variety of acute infections in its hosts, and multidrug-resistant strains present significant challenges to public health and animal husbandry. Therefore, it is necessary to explore new drug targets to control E. coli epidemics. Previous studies have reported that ppk mutants of Burkholderia pseudomallei and Mycobacterium tuberculosis are more susceptible than the wild types (WTs) to stress. Therefore, we investigated the stress response to antibiotics mediated by polyphosphate kinase (PPK) in ExPEC strain PCN033. We observed that planktonic cells of a ppk knockout strain (Δppk) were more susceptible to antibiotics than was WT. However, biofilm-grown Δppk cells showed similar susceptibility to that of the WT and were more tolerant than the planktonic cells. During the planktonic lifestyle, the expression of genes involved in antibiotic tolerance (including resistance-conferring genes,and antibiotic influx and efflux genes) did not change in the Δppk mutant without antibiotic treatment. However, the resistance-conferring gene bla and efflux genes were upregulated more in the WT than in the Δppk mutant by treatment with tazobactam. After treatment with gentamycin, the efflux genes and influx genes were upregulated and downregulated, respectively, more in the WT than in the Δppk mutant. The expression of genes involved in biofilm regulation also changed after treatment with tazobactam or gentamycin, and which is consistent with the results of the biofilm formation. Together, these observations indicate that PPK is important for the antibiotic stress response during the planktonic growth of ExPEC and might be a potential drug target in bacteria.